Lumbosacral plexus lesions: correlation of clinical signs and computed tomography. Issue 1 (January 1988) - Vock, P; Mattle, H; Studer, M; Mumenthaler, M
Abstract : Neurological signs and computed tomographic morphology were compared in 60 patients. The primary neurological deficit was most commonly located in the sacral (n = 31) or lumbar plexus (n = 23) and was most commonly caused by a neoplasm (n = 40). In 78% of the patients it correlated with the lesions detected by computed tomography (CT). CT reliably demonstrates extraspinal mass lesions, but only moderately well predicts functional signs.